PERSEPSI PENGEMIS TENTANG PERDA NO. 12 TAHUN 2008 - Putri Junita Anipa; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Higt level of urbanization creates a number of social problem in cyti. Urbanization happens due to hard living of suburban people. Sububar people move to cities to get a better economy and living, many people choose to move to cities, as the effect working fields in cities decrease, and the competition in creases. Suburban people who moved to cities don’t get a proper job, as aresult, they chose to be beggars. Pekanbaru is one of the cities where we can find a lot of beggars. Not even local government's rule (perda no 12 year 2008) can make beggars stop their activity. Writer did this qualitative research for figuring out the factors that influence a beggar in doing this such activity. This research is also for figuring out if beggars' perception have influence in decreasing beggig activity in Pekanbaru.Keywords: Beggars, poverty, local rules